Strengthening the Moral of Students Through PPKN Learning - Adha , Chalijah; Izzatunnisa, Izzatunnisa; Nasution, Abdul Gani Jamora (IKAMAS: Manajemen Pendidikan Islam, 2023)
Moral education is education that must be instilled in children. The age of elementary school children is golden period to apply learning to form the morals and character of these students. Civics is a subject that is expected to be a means for teachers to educate and shape the morals and characteristics of each student. The formation of good character and morals will produce positive sides for a child, one of which is the growth of a sense of responsibility , courtesy and discipline. Factors that can affect the morale of a child are the environment, friends, as well as media and technology